Research and practice of blended teaching mode based on smart classroom - Jiang Cuiyuan (ITM Web of Conferences)
With the further development of education informatization, the integration of smart classroom and blended teaching has become an important direction of educational innovation. With the help of smart classroom and Super Star Learning teaching platform, this paper explores the online and offline mixed teaching mode based on smart classroom, and builds a classroom teaching system of "one point, two lines and three stages". The model is applied to the course "Android Mobile Application Development". The results show that the blended teaching under the smart classroom improves students' academic performance, with high satisfaction and enhanced students' hands-on ability. The online learning behavior is proportional to the final score. This proves to a certain extent that the integration of smart classroom into blended teaching can promote teaching reform and innovation and improve teaching quality.